Incidence of leaf diseases in the agroforestry systems at Yurimaguas, Peru - Aragón, L. (2022)
An agroforestry system (SAF) is characterized by having a diversity of components, such as timber and non-timber forest species and crops, pastures, or a livestock production system. This diversity of components in the system reduces the intensity of diseases, e.g. foliar diseases. This study aimed to detect the fungal microorganisms associated with the leaf spots of plant species that are part of the agroforestry production systems of the Peruvian farmers from Yurimaguas and to determine the level of incidence of the leaf spots in the systems of agroforestry production. Different land cropping systems were implemented in the farms, such as palm (Bactris gasipaes) to produce palm hearts, cocoa (Theobroma cacao), and plantain (Mussa sp.). Also, silvopastoral systems with fast and slow growing timber species and cattle with pastures for grazing and reforestation in areas of secondary forests in a state of degradation. Prospecting, collecting, and determining the incidence of diseases in each farm were carried out and later they were identified with molecular methods using the primers ITS 1 and ITS 4. The symptoms predominantly observed were, leaf spots in cocoa (rootstock), palm, and plantain. Symptoms like wilting, decline, or rot were not observed. The incidence was evaluated in two collection periods (2018 and 2019). The fungi isolated from the leaf spots were Pestalotiopsis sydowiana and Colletotrichum siamense as causative agents of leaf spots on palm and cocoa, and Mycosphaerella fijiensis on plantain. When determining the incidence from April 2018 to October 2019, a decrease in this parameter (incidence) was observed for farms with palm, especially in those where the production system was improved by the use of fertilizants as a requirement of the crop. It was concluded that the highest intensity of foliar diseases occurred in agricultural systems with monoculture of palm with 100 % at the beginning of the evaluation, and for agroforestry systems in the silvopastoral prototype, it was only detected in a range of 0 % to 25 %.